(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This paper explores the phraseological systems of English and Uzbek, focusing on their semantic organization and typological distinctions. Phraseology — which includes idioms, proverbs, and set expressions — mirrors a nation’s worldview, creative thinking, and cultural values. Through a comparative approach, the study uncovers both universal tendencies and culture-specific traits. The results demonstrate that while idioms in both languages share metaphorical and context-dependent qualities, they diverge in imagery, symbolic interpretation, and pragmatic use. The research emphasizes that phraseology plays a crucial role not only in theoretical linguistics but also in translation studies, intercultural communication, and the methodology of foreign language teaching.